2002
DOI: 10.1046/j.1365-2745.2002.01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Atopic allergy and delayed type hypersensitivity in Estonian children

Abstract: In this group of children our findings do not support the hypothesis of an immune deviation with decreased Th1 and increased Th2 responses leading to atopic disease, but rather a process of immune modulation whereby both Th1 and Th2 responses are increased in atopic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Nevertheless, several subsequent studies in different populations have failed to demonstrate any association between atopic disorders and tuberculin responsiveness (20–23), and some studies even revealed stronger responses to mycobacteria among allergic children (14, 24). Similarly, in a recent Estonian study, delayed‐type hypersensitivity responses to diphtheria and tetanus antigen were stronger in atopic children (25).…”
mentioning
confidence: 66%
“…Nevertheless, several subsequent studies in different populations have failed to demonstrate any association between atopic disorders and tuberculin responsiveness (20–23), and some studies even revealed stronger responses to mycobacteria among allergic children (14, 24). Similarly, in a recent Estonian study, delayed‐type hypersensitivity responses to diphtheria and tetanus antigen were stronger in atopic children (25).…”
mentioning
confidence: 66%
“…6 10 However, some authors argue that the available epidemiological evidence may not provide support for this mechanism of early immune deviation and have suggested that the environmental influences on atopic disease are likely to occur throughout the life. 17 18 The present study was planned to investigate whether the effect of the farming environment on sensitisation to common allergens is restricted to early childhood or exists throughout life. In Finnish farms, women traditionally take care of cattle and previous studies have suggested that contact with animals is essential for the protective farm effect.…”
mentioning
confidence: 99%
“…The quoted work [17] points out that both the T(H1) and the T(H2) response might be disturbed in allergy sufferers, and this then results in allergies and infections. Fitting into this picture, the quoted study [18] shows that sensitized test persons show not only an increased T(H2) response, but also an increased T(H1) response (to diphtheria and tetanus toxins).…”
Section: Correlations Between Infections and Allergies/asthmamentioning
confidence: 89%